Enhancement Of Light-matter Interaction In Topological Waveguides And Resonators - Brauckmann, Michael; Narvaez Castaneda, Emmanuel; Siebert, Dustin; Brecht, Benjamin; Förstner, Jens; Zentgraf, Thomas (Proceedings of The 15th International Conference on Metamaterials, Photonic Crystals and Plasmonics)

Estimation of losses caused by sidewall roughness in thin-film lithium niobate rib and strip waveguides - Hammer, Manfred; Babel, Silia; Farheen, Henna; Padberg, Laura; Scheytt, J. Christoph; Silberhorn, Christine; Förstner, Jens (Optics Express)
Samples of dielectric optical waveguides of rib or strip type in thin-film lithium niobate (TFLN) technology are characterized with respect to their optical loss using the Fabry-Pérot method. Attributing the losses mainly to sidewall roughness, we employ a simple perturbational procedure, based on rigorously computed mode profiles of idealized channels, to estimate the attenuation for waveguides with different cross sections. A single fit parameter suffices for an adequate modelling of the effect of the waveguide geometry on the loss levels.
Keywords: tet_topic_waveguide

From Swiss-cheese to discrete ferroelectric composites: assessing the ferroelectric butterfly shape in polarization loops - Myroshnychenko, Viktor; Mulavarickal Jose, Pious Mathews; Farheen, Henna; Ejaz, Shafaq; Brosseau, Christian; Förstner, Jens (Physica Scripta)
We explore the polarization hysteretic behaviour and field-dependent permittivity of ferroelectric-dielectric 2D materials formed by random dispersions of low permittivity inclusions in a ferroelectric matrix, using finite element simulations. We show how the degree of impenetrability of dielectric inclusions plays a substantial role in controlling the coercive field, remnant and saturation polarizations of the homogenized materials. The results highlight the significance of the degree of impenetrability of inclusion in tuning the effective polarization properties of such ferroelectric composites: coercive field drops significantly as percolation threshold is attained and remnant polarization decreases faster than a linear decay.
Keywords: tet_topic_ferro

Symmetry-protected TM modes in rib-like, plus-shaped optical waveguides with shallow etching - Üstün, Necati; Farheen, Henna; Hammer, Manfred; Förstner, Jens (Journal of the Optical Society of America B)
Lateral leakage of TM modes in dielectric optical waveguides of rib/ridge or strip-loaded types can be fully suppressed, if the waveguide core is formed not through a strip that protrudes at one side (up) from the remaining lateral guiding slab, but through parallel strips on both sides (up and down), such that the resulting cross section becomes vertically symmetric. The fairly general arguments underlying the leakage suppression apply to TM modes of all orders simultaneously, and are independent of wavelength. These plus-shaped waveguides support strictly guided, non-leaky TM modes for, in principle, arbitrarily shallow etching.
Keywords: tet_topic_waveguide

An efficient compact blazed grating antenna for optical phased arrays - Farheen, Henna; Joshi, Suraj; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Journal of Physics: Photonics)
Phased arrays are vital in communication systems and have received significant interest in the field of optoelectronics and photonics, enabling a wide range of applications such as LiDAR, holography, wireless communication, etc. In this work, we present a blazed grating antenna that is optimized to have upward radiation efficiency as high as 80% with a compact footprint of 3.5 μm × 2 μm at an operational wavelength of 1.55 μm. Our numerical investigations demonstrate that this antenna in a 64 × 64 phased array configuration is capable of producing desired far-field radiation patterns. Additionally, our antenna possesses a low side lobe level of -9.7 dB and a negligible reflection efficiency of under 1%, making it an attractive candidate for integrated optical phased arrays.
Keywords: tet_topic_opticalantenna

Guided modes of thin-film lithium niobate slabs - Hammer, Manfred; Farheen, Henna; Förstner, Jens (Optics Continuum)
Dielectric slab waveguides made of thin-film-lithium-niobate (TFLN) media are consid-ered, for operation in the linear regime. We outline and implement a largely analytic procedure forrigorous modal analysis of three-layer slabs with birefringent, anisotropic core. For Z-cut wave-guides, the slab eigenmode problem separates into uncoupled sets of scalar equations for TE andTM modes. Slabs in X-cut configuration support mostly mildly hybrid eigenmodes, with clear pre-dominant TE or TM polarization, and with effective indices that depend on the propagation directionof the modes, relative to the crystal axes. Strong hybridization can be observed for near degeneratemodes in singular configurations without vertical symmetry, or in symmetric slabs where two nearlydegenerate modes are of the same symmetry class. Dispersion curves for slab thickness and propa-gation angle are discussed, for slabs with oxide and air cover.
Keywords: tet_topic_waveguide

Evaluation of Measurement Noise Effects in the Close Environment of Equivalent Near-Field Sources - Schröder, Dominik; Kiefner, Ulrich; Hedayat, Christian; Förstner, Jens (2024 International Symposium on Electromagnetic Compatibility – EMC Europe)
Based on the surface equivalence principle an equivalent near-field source can be determined by measurements with a near-field scanner. One application is to use the source to simulate the interferences of the device-under-test with other objects in its close environment. Due to a limited signal-to-noise ratio in practical applications, noise adds to the near-field source. Hence, noise effects affect the quality of the simulation results and cause uncertainties. The influence of the noise effects is investigated by a simulative approach with artificially added noise. Two test devices with different a geometric dimension, operating frequency and excited power are evaluated for different characteristics and signal-to-noise ratios to assess the impact of the simulation results. Finally, in a combined simulation an equivalent near-field source will disturb an IoT-device and the voltages at two resistors on the device are examined.
Keywords: tet_topic_hf; tet_enas

On‐Demand Indistinguishable and Entangled Photons Using Tailored Cavity Designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan (Advanced Quantum Technologies)
Abstract The biexciton‐exciton emission cascade commonly used in quantum‐dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work, it focuses on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishability. It achieves this goal by selectively reducing the biexciton lifetime with an optical resonator. It demonstrates that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and twofold degenerate optical modes. The in‐depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum‐dot cavity excitation dynamics with full access to photon properties. It reports non‐trivial dependencies on system parameters and use the predictive power of the combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values, here specifically for the telecom C‐band at 1550 nm.
Keywords: tet_topic_qd

On-demand indistinguishable and entangled photons at telecom frequencies using tailored cavity designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan
The biexciton-exciton emission cascade commonly used in quantum-dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work we focus on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishibility. We achieve this goal by selectively reducing the biexciton lifetime with an optical resonator. We demonstrate that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and two-fold degenerate optical modes. Our in-depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum-dot cavity excitation dynamics with full access to photon properties. We report non-trivial dependencies on system parameters and use the predictive power of our combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values in the telecom C-band at $1550\,nm$.
Keywords: tet_topic_phc; tet_topic_qd

Optimized, Highly Efficient Silicon Antennas for Optical Phased Arrays - Farheen, Henna; Strauch, Andreas; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
Silicon photonics, in conjunction with complementary metal-oxide-semiconductor (CMOS) fabrication, has greatly enhanced the development of integrated optical phased arrays. This facilitates a dynamic control of light in a compact form factor that enables the synthesis of arbitrary complex wavefronts in the infrared spectrum. We numerically demonstrate a large-scale two-dimensional silicon-based optical phased array (OPA) composed of nanoantennas with circular gratings that are balanced in power and aligned in phase, required for producing elegant radiation patterns in the far-field. For a wavelength of 1.55 μm, we optimize two antennas for the OPA exhibiting an upward radiation efficiency as high as 90%, with almost 6.8% of optical power concentrated in the field of view. Additionally, we believe that the proposed OPAs can be easily fabricated and would have the ability to generate complex holographic images, rendering them an attractive candidate for a wide range of applications like LiDAR sensors, optical trapping, optogenetic stimulation, and augmented-reality displays.
Keywords: tet_topic_opticalantenna